FAKTOR YANG MENENTUKAN LOYALITAS NASABAH PADA BANK BNI SYARIAH (STUDI KASUS NASABAH BANK BNI SYARIAH CABANG FATMAWATI) - Yunia Silvia Sesunan; Ligar Fadilah (Sekolah Tinggi Ilmu Ekonomi Bisnis Indonesia, 2018)
The purpose of this study was to observe the effect of marketing mix, brand image, servicequality and loyalitas of the customer's Bank BNI Syariah Branch Fatmawati. The data that used inthis study is primary data, and data collection is done using questionnaire with random samplingmethode,the object of this research is the customerof Bank BNI Syariah Fatmawati Branch. In orderto provide the best service to the customer. The result of this study indicates that marketing mix,brand image and service qualityhave positive and significant partial and simultaneous effect oncustomer loyalty of Bank BNI Syariah Branch Fatmawati.